Recent Archaeological Research in Turkey: Exploration and Excavations in the District of Islâhiye - Alkım, U. Bahadır
Tilmen Hüyük; Gedikli; Karahüyük; road over the Amanus: Hassa-Tiyek-pass of Tiyek-Çardak-Yaylası-Domuz Damı-Taşpınar-Taştekne-Civik-Dörtyol. Most likely used by the Assyrians.